Analysis on Operation Value of Electrochemical Energy Storage and Pumped Storage Participating in a Joint Market - Yi LIN; Wei LIN; Wei WU; Yuewen JIANG; Azhu LIN (Zhongguo dianli)
To evaluate the operation value of electrochemical energy storage and pumped storage participating in the power market, clarify the cost-benefit mechanism of energy storage, and promote the development and application of the energy storage business model, this paper constructs a joint clearing optimization model of power market, frequency regulation market and reserve market, and applies the electrochemical energy storage and pumped storage to the joint market as the dispatching management tools of the market operators. According to the changes in the total market cost and the daily operating cost of energy storage before and after the participation of energy storage in the joint market, the operational values of energy storage in the joint market is quantitatively compared. The impacts of the two types of energy storage on the market clearing price and the main factors affecting the operational value of energy storage are analyzed through a case study, so as to provide reference for the planning, construction and operation of energy storage.